Review articles on soccer performance analysis: a bibliometric analysis of current trends and emerging themes - Plakias, S. (Sports, 2025)
Objectives: This study aimed to analyze review articles on soccer performance analysis (PA) using a bibliometric approach to address three main research questions: (a) How has the publication of review articles related to soccer PA evolved over time? (b) Which authors and journals have been the most influential in this field and what are the collaboration networks between them? (c) What are the dominant topics, methodological issues, and gaps in the relevant literature?